2019
DOI: 10.1016/j.scitotenv.2018.09.251
|View full text |Cite
|
Sign up to set email alerts
|

Non-native freshwater fauna in Portugal: A review

Abstract: We reviewed information on nonnative freshwater fauna in Portugal.• Fish and mollusks are the taxonomic groups with more established species. • Most species are native from other regions of Europe and North America. • The Portuguese and EU legislation showed large discrepancies in its invasive species. • We identified invaders for which legislation and actions are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 129 publications
(112 reference statements)
1
35
0
Order By: Relevance
“…The high level of parental care in this species contributes to high recruitment and establishment success but, unlike for most native species, the larvae do not easily disperse to novel locations, which is confirmed by the lack of larvae collected in previous larval ecology studies [43]. In addition, the vast distribution indicates a wide tolerance to biotic and abiotic factors, a hallmark of a successful invasive species [44][45][46][47]. In Mediterranean-type streams, such as those where A. facetus is found, the fish assemblages are confined to pools, with low flow and loss of connectivity, increasing the pressure from competition and predation (including from terrestrial animals and the avifauna) [48,49].…”
Section: Distribution Of a Facetus In Southern Portugalmentioning
confidence: 73%
See 1 more Smart Citation
“…The high level of parental care in this species contributes to high recruitment and establishment success but, unlike for most native species, the larvae do not easily disperse to novel locations, which is confirmed by the lack of larvae collected in previous larval ecology studies [43]. In addition, the vast distribution indicates a wide tolerance to biotic and abiotic factors, a hallmark of a successful invasive species [44][45][46][47]. In Mediterranean-type streams, such as those where A. facetus is found, the fish assemblages are confined to pools, with low flow and loss of connectivity, increasing the pressure from competition and predation (including from terrestrial animals and the avifauna) [48,49].…”
Section: Distribution Of a Facetus In Southern Portugalmentioning
confidence: 73%
“…Although this neotropical cichlid seems to be restricted to a few basins in southern Portugal, its local abundance seems to be increasing. Despite being limited to a few sample sites, this species was dominant (abundance and biomass) in fish fauna already threatened by human activities, and poor in native but highly endemic species [45,58,60]. During the hot and dry summers in Mediterranean regions [61], such as southern Portugal, the fish fauna can be trapped in pools where the temperature increases rapidly and the dissolved oxygen decreases during the day, and even more at night when algae or plants are present; concomitantly, the resources diminish and, thus, the competition increases.…”
Section: Evaluation Of the Toolkits And Reasons For Increased Invasivmentioning
confidence: 99%
“…Finally, as a consequence of global warming, and water deviation for irrigation and livestock, a reduction in water availability is expected in pools in the coming years [14] further increasing the pressure on U. delphinus.…”
Section: Discussionmentioning
confidence: 99%
“…[8]. Invasive bivalves may often become dominant (by attaining high density and biomass rapidly [9,10]), and therefore alter the community structure and function of invaded systems [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study (Ribeiro et al, 2019) conducted in Portugal based on a self-administered questionnaire showed that high consumption rate of fish (between daily, and a minimum of three times a week), was reported by 47% of the respondents.…”
mentioning
confidence: 99%